Development of water adsorbent from spent bleaching earth for dehydration of azeotrope ethanol- water mixture - Azharin Shah, Abd Aziz (2017)
SBE is a waste from palm oil refinery it is normally dumped into landfill. Ethanol is an alternative fuel and it must be anhydrous to be used in petrol driven engine. In this study, water adsorbent to dehydrate the azeotrope mixture of ethanol-water was synthesised from SBE using modified fusion method. The synthesised water adsorbent was characterized using XRD, FESEM-EDX, ICP-MS and surface area and porosity analyser. Six variables or factors (i.e. added alumina, aging time, aging temperature, added KOH, added water and fusion temperature) affecting the water-uptake were studied using OVAT technique followed by structured full multilevel factorial DOE method. Lastly, the synthesised and commercial water adsorbent was used to dehydrate azeotrope mixture of ethanol-water in bench top adsorption apparatus to produce dehydrated ethanol. XRD analysis showed that the water adsorbent was not the type of zeolite A. However from SEM images, it was believed that the water adsorbent consist of several types of phases such as zeolite A, X, MFI plus amorphous phase. No relationship was found between results from surface area and porosity experiments to the water-uptake capacity of the water adsorbent. Using OVAT technique, the best added alumina was found to be 80 g/100 g material, aging time of 5 days, aging temperature of 80oC, added KOH of 71% of material mass, fusion temperature was 550oC and the best added water was 65% of the weight of ground fused material. Analysis of variant of the DOE technique showed that the main effects of added alumina, added water, fusion temperature and aging time were significant. There were two way interaction effects between fusion temperature and aging temperature, and between fusion temperature and aging time. The best variables combinations were at fusion temperature of 550oC, 80oC aging temperature, 3 days of aging time, added water 65% wt, added KOH 56% of material mass and added alumina 80 g alumina/g material, with the expected water-uptake of 0.0343 g H2O/g adsorbent. Yoon and Nelson model can be used to model the experimental dehydration curve for prediction of breakthrough time. The performance of synthesised water adsorbent was approximately 66% of the commercial water adsorbent in terms of breakthrough time. This study showed that low cost water adsorbent can be produced from spent bleaching earth using modified fusion method and was able to dehydrate ethanol-water mixture more than 99% weight ethanol to be used as bio-fuel in petrol driven engine.